Race and Space in the Postcolony: A Relational Study on Urban Planning Under Racial Capitalism in Brazil and South Africa - Melgaço, Lorena (2022)
This article analyzes two planned cities—Belo Horizonte (Brazil) and Bloemfontein (South Africa)—to investigate connectivities across geographies and temporalities and reveal the role of urban planning in racial capitalism. Early works in urban sociology underscore the color line in producing differentiation in capitalist development. But color-blind analyses of capitalism have undermined the role of race in the urbanization process and formation of value—of places and people—and how the modern triad—colonial, racial, and capital—is deeply implicated in power modalities. Based on policy analysis, we historicize political choices in discuss urban planning and national developmentalist schemes after redemocratization that produced racial-spatial inequalities. We argue that color-blind urban policies still neglect the role of race in the production of Brazilian and South African cities under the guise of “planning innocence.” This discussion expands our understanding of urbanization and capital accumulation as a dialectical process of black dispossession and the protection of white property in the postcolony.